SUCCESSFUL TREATMENT OF DERMATOPHYLOSIS USING HOMEOPATHY MEDICINES IN COWS - Kalirajan, R; Rumarani, R (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Six pluriparous Holstein Friesian cross bred cows of age between 4 years to 6 years with dermatophilosis were examined and treated with Homeopathic medicines.Direct microscopic examination of the impression smears of skin lesions and bacterial culture confirmed the organisms D. congolensis. The animals were treated with homeopathic medicines, Rhus tox 30 C, Sepia 30 C, Thuja 200X and Psorinum 30 C. Treated animals showed cessation of itching, oozing and shedding off scabs from 3rd day to 5th day and the crusts started falling off from the lesions between 3rd to 4th day of treatment. Hair regrowth started from 12 days and complete healing without any scarring was observed within 25 to 28 days . The disease did not recur on the treated animals during the follow up period of one year even during the next rainy season.
Keywords: Cows-Dermatophilosis; Homeopathic medicines